Effect of crude extracts of tulbaghia violacea (wild garlic) on growth of tomato and supression of meloidogyne species - Malungane, Molebatsi Mlungisi Florah (University of Limpopo, 2014)
The management of root-knot nematodes (Meloidogyne spp.) has become a challenging task in tomato (Solanum lycorpesicum) production, due to the withdrawal of effective chemical nematicides. Currently, crude extracts of different plant species are being researched as alternative to chemical nematicides, with promising results. The objective of this study was to determine the effect of crude extracts of wild garlic (Tulbaghia violacea) on the growth of tomato under greenhouse conditions, and the suppression of M. incognita race 2 population densities. Treatments consisted of four levels of crude extracts viz. 0, 2, 4 and 8 g per pot, were arranged in a randomised complete block design with 10 replicates. Seedlings were inoculated with 1000 juveniles of M. incognita race 2 at transplanting and treated with crude extracts two days later. At 56 days, the crude extract of T. violacea increased plant height, stem diameter, number of cluster, flowers, fruits and leaves by 43-73%, 108-200%, 57-81%, 55-110%, 170-223% and 51-66%, respectively. It also increased the root mass and shoot mass by 95% and 96%, respectively. Crude extracts of T. violacea did not have any effect on soil pH and electrical conductivity (EC). Crude extracts of T. violacea consistently reduced population densities of M. incognita race 2 by 50, 64 and 73% in roots at 2, 4 and 8 g crude extracts, respectively and by 21, 30 and 58% in soil at similar levels, respectively. In conclusion, crude extracts of T. violacea have the potential to improve growth of tomato plants and suppress population densities of M. incognita race 2 and could be used as botanical nematicide in tomato production.
Thesis (M.Sc. Agriculture (Plant Production)) -- University of Limpopo, 2014
Keywords: Tomato production.; Wild garlic; Garlic; Allium vineale